Reproductive Health Services and Quality of Health Status of Woman in Kyanamira Sub-County Kabale District. - Atwongyeire, Precious (Kabale University, 2024)
The study aimed at the reproductive health services and quality of health status of women in the Kyanamira sub-county. The Study followed research objectives which were to identify the contribution of reproductive health services and the quality of health status of women in the Kyanamira sub-county Kabale District to find out the challenges faced by rural women in accessing reproductive health and quality of health services in Kyanamira sub county Kabale District and to suggest possible solutions to the chal enges faced by women in accessing reproductive health services in Kyanamira sub county Kabale District. The methodology of the study was a descriptive research design using both qualitative and quantitative tools. A sample size of 80 respondents was selected from respondents of Kyanamira sub-county Kabale district. The study recommends that; Based on the results obtained in this study, it is recommended that Based on the results obtained in this study, it is recommended that strengthening the agencies for spreading the services of reproductive health quality of health status by giving them enough education on how to get engaged in reproductive health services. Community sensitization on how to review some of the counseling and testing procedures so as to encourage reproductive mothers to test on before giving birth and there is need for government intervention on reproductive health care services among adolescent mothers and quality of health status with in Kyanamira sub-county Kabale district and people should join in the fight against sexual transmitted diseases by not cooperate with ignorance or primitive mothers on individuals and officials basis, Basing on study objectives, the study included that there were the importance of reproductive health services and quality of health status of Women in Kyanamira sub-county Kabale district as they included: health care quality, increased mortality rate, hospital committee, early detection, behavioral change, age of an individual, famil y influence, stigma and cervical education with, were chal enges faced by reproductive health care services by women in Kyanamira sub-county Kabale district as they included; poverty, trust, culture, care, lack of government concern, ignorance, family size and lack of access to informa t ion and possible ways in which Reproductive health services and quality of health status of women can be strengthen its services in Kyanamira sub-county Kabale district as they included; palative care, clinical care, spiritual care, social care, psychological support, government concern and community sensitization.